PEMAHAMAN KONSUMEN MUSLIM DAN RELIGIUSITASNYA: PENGARUHNYA TERHADAP LABEL HALAL AROMA PRIMA BAKERY & CAKE SHOP - Kartika, Dinda Ayu; Siregar, Pani Akhiruddin (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
This research aims to prove the hypothesis that Muslim consumer understanding and religiosity, these two independent variable, have a significant influence on the halal label of Aroma Prima Bakery & Cake Shop which is the dependent variable. The research method uses quantitative data analysis, where the researcher, collected primary data by distributing questionnaires to 97 Muslim consumer who purchased bread at the Aroma Prima Bakery & Cake Shop. The data were processed with the help of SPSS version 21. Afterwards, it was regressed using multiple linear regression analysis model. The sampling technique used was insidental sampling. The research results concluded if Muslim consumer understanding and their religiosity, these two independent variable have a significant influence on their dependent variable, the halal label of Aroma Prima Bakery & Cake Shop. These two independent variable support the research hypothesis, which accepts H1 and H2 for their dependent variable. This research serves as a reference, a moral guide, and a sustainable model development so that Aroma Prima Bakery & Cake Shop is always responsive in including the Indonesian halal label on every bread package produced.